Cover Image. (6th February 2019) - Rio‐Echevarria, Iria M.; Ponti, Jessica; Bogni, Alessia; Gilliland, Douglas; Altissimo, Matteo; Pascolo, Lorella; Ceccone, Giacomo; Gianoncelli, Alessandra
Abstract : The cover image is based on the Research Article XRF mapping and TEM analysis of coated and uncoated silica nanoparticles in A549 cells and human monocytes, by Iria M. Rio‐Echevarria et al., https://doi.org/10.1002/xrs.2999 . Acknowledgments: Dr. George Kourousias (Elettra Sincrotrone Trieste).